2012
DOI: 10.7150/ijbs.3723
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bovine Induced Pluripotent Stem Cells by Lentiviral Transduction of Reprogramming Factor Fusion Proteins

Abstract: Pluripotent stem cells from domesticated animals have potential applications in transgenic breeding. Here, we describe induced pluripotent stem (iPS) cells derived from bovine fetal fibroblasts by lentiviral transduction of Oct4, Sox2, Klf4 and c-Myc defined-factor fusion proteins. Bovine iPS cells showed typical colony morphology, normal karyotypes, stained positively for alkaline phosphatase (AP) and expressed Oct4, Nanog and SSEA1. The CpG in the promoter regions of Oct4 and Nanog were highly unmethylated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 18 publications
3
75
1
Order By: Relevance
“…Speculatively, bovine iPSCs may need NANOG on top of OSKM, and FGF and knockout serum to maintain the pluripotency status (Han et al, 2011). The exogenous genes used for reprogramming in the current study were not silenced as reported in previous studies in which viral vectors had been used for reprogramming (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Speculatively, bovine iPSCs may need NANOG on top of OSKM, and FGF and knockout serum to maintain the pluripotency status (Han et al, 2011). The exogenous genes used for reprogramming in the current study were not silenced as reported in previous studies in which viral vectors had been used for reprogramming (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Previously, bovine iPSCs have been derived from bovine fetal and adult fibroblasts by retroviral or lentiviral transduction (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011) or nonintegrating plasmids (Huang et al, 2011;Wang et al, 2013). Retroviral and lentiviral vectors are the most commonly used gene delivery systems because they have high transduction rates; lentiviral vectors even allow transduction of nonproliferating cells (Coroadinha et al, 2010;Segura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations